Influence of Materialism on Impulse Buying Among Indian Millennials: Does Income Matter? - Sen, Shaon; Nayak, Smitha (Indian Journal of Marketing, 2019)
The research paper attempted to examine the influence of materialism on impulse buying among the Indian millennials and the role of family income in moderating this relationship. This research was undertaken during January-May 2019. A structured online questionnaire was used to collect data from the millennial age group. Consequently, 404 complete responses were analyzed using AMOS 22 and SPSS 20. The research findings posited that Indian millennials were materialistic and displayed impulse buying under the influence of materialism. The three dimensions of materialism studied here included success, centrality, and happiness. Among the three dimensions of materialism, centrality showed the strongest influence on impulse buying (Î² = 0.267, p < 0.1). Family income had no significant relationship with impulse buying; hence, had no moderating effect on the materialism-impulse buying relationship. It was also observed that age progression retarded the probability of engaging in impulse buying. These research findings would equip retailers to better understand the millennial segment as they contribute significantly to the texture of the Indian population and the market space.